End‐to‐end application of model‐informed drug development for ertugliflozin, a novel sodium‐glucose cotransporter 2 inhibitor. (15th May 2021) - Fediuk, Daryl J.; Nucci, Gianluca; Dawra, Vikas K.; Callegari, Ernesto; Zhou, Susan; Musante, Cynthia J.; Liang, Yali; Sweeney, Kevin; Sahasrabudhe, Vaishali
Abstract: Model‐informed drug development (MIDD) is critical in all stages of the drug‐development process and almost all regulatory submissions for new agents incorporate some form of modeling and simulation. This review describes the MIDD approaches used in the end‐to‐end development of ertugliflozin, a sodium‐glucose cotransporter 2 inhibitor approved for the treatment of adults with type 2 diabetes mellitus. Approaches included (1) quantitative systems pharmacology modeling to predict dose–response relationships, (2) dose–response modeling and model‐based meta‐analysis for dose selection and efficacy comparisons, (3) population pharmacokinetics (PKs) modeling to characterize PKs and quantify population variability in PK parameters, (4) regression modeling to evaluate ertugliflozin dose‐proportionality and the impact of uridine 5'‐diphospho‐glucuronosyltransferase (UGT) 1A9 genotype on ertugliflozin PKs, and (5) physiologically‐based PK modeling to assess the risk of UGT‐mediated drug–drug interactions. These end‐to‐end MIDD approaches for ertugliflozin facilitated decision making, resulted in time/cost savings, and supported registration and labeling.